Qualitative and quantitative evaluation of water resources that feed into the National Park Igneada Longoz Forests (Turkish Thrace) by using physico-chemical and biological analyses - Camur-Elipek, Belgin; Kirgiz, Timur; Oterler, Burak; Tas, Menekse (HIDROBIOLÓGICA, 2016)
In this study, some physico-chemical and biological features of the water resources that feed three alluvial longose groves (are also known as Longoz) which are important wetlands in the National Park Igneada Longoz Forests including a lot of different ecosystems were investigated. In order to assess the water quality, a total of eight running water resources were sampled within four different seasons and two lakes were sampled at dry and wet seasons in 2008-2009. While some water resources were found to have high quality levels for some physico-chemical findings, the results were also supported by using EPT (Ephemeroptera Plecoptera Trichoptera) index. Furthermore, the cluster analysis, correspondence analysis, and Pearson correlation index were used to determine the relationships between the data. As a result, although a lot of sampled water resources that feed into the National Park area has been found to have good quality level, it was also observed that the area have been under the negative effects of humans. Therefore, at the end of this study, it was also made some suggestions for sustainable usage of this special area.